The Relationship Between Social Media Use and Mental Health Among Adolescents at SMP Negeri 11, Kupang - Ninef, Violin Irene; Ndun, Felipus Stefen; Ansar, Asmawati; Andung, Rusdiyanto Randja; Saputri, Ni Made Ayu Dinda (INDOGENIUS, 2025)
Background & Objectives: The advancement of information and communication technologies, especially social media, has significantly impacted daily life, particularly among adolescents. This age group is particularly vulnerable to mental health disorders such as anxiety, depression, and stress due to excessive social media use. This study aims to investigate the relationship between social media use and mental health among adolescents at SMP Negeri 11 Kupang. Methods: This quantitative research adopts a cross-sectional design. The population consists of all students at SMP Negeri 11 Kupang. A sample of 100 students was randomly selected. Data was collected via questionnaires that assessed the frequency and intensity of social media use, as well as mental health indicators (anxiety, depression, stress). Data analysis was performed using descriptive and inferential statistics, specifically Pearson correlation tests. Results: There is a significant relationship between the frequency and duration of social media use and levels of anxiety, depression, and stress in students. Sixty percent of students who use social media for more than 4 hours a day show higher levels of mental health symptoms compared to those who use it less than 2 hours per day. Conclusion: Excessive social media use has a negative impact on adolescent mental health. Therefore, it is necessary to provide education and supervision from both parents and schools on the healthy and wise use of social media.